Метод "сортуючої” кластеризації (DRSA) для класифікації рослинності - Гончаренко, І.В. (Доповіді НАН України, 2015)
Розглянуто застосування нового методу класифiкацiї фiтоценозiв “distance-ranked sorting
assembling” (DRSA). Проаналiзовано аспекти стiйкостi фiтоценотичної класифiкацiї. Показана можливiсть варiювання масштабу кластеризацiї та кiлькостi фiтоценотичних кластерiв, класифiкацiї даних широкого екологiчного дiапазону та об’єктивiзацiї визначення екотонних угруповань. Якiсть геоботанiчної класифiкацiї запропоновано оцiнювати кiлькiстю статистично вiрних видiв. Рассмотрено применение нового метода классификации фитоценозов “distance-ranked sorting
assembling” (DRSA). Проанализированы аспекты устойчивости фитоценотической классификации. Показана возможность варьировать масштаб кластеризации и количество фитоценотических кластеров, классифицировать данные широкого экологического диапазона
и объективизировать определение экотонных сообществ. Качество геоботанической классификации предложено оценивать количеством статистически верных видов. The application of a new clustering technique, named “distance-ranked sorting assembling” (DRSA),
for the classification of plant communities is considered. Aspects of the stability of a phytocoenotic
classification are analyzed. It is shown that a researcher can vary the scale of clustering and thus
change the number of phytocoenons, classify reasonably the data of a wide environmental amplitude,
and determine objectively ecotonic releves among the data. We suggest to use the quantity of faithful
species per phytocoenon for qualifying clusters in the field of geobotany.